Olfactory Cues in Infant Feeds: Volatile Profiles of Different Milks Fed to Preterm Infants - Muelbert, Mariana; Bloomfield, Frank H.; Pundir, Shikha; Harding, Jane E.; Pook, Chris (Frontiers in Nutrition, 2021)
Background: Smell is determined by odour-active volatile compounds that bind to specific olfactory receptors, allowing us to discriminate different smells. Olfactory stimulation may assist with digestion and metabolism of feeds in the neonate by activation of the cephalic phase response of digestion. Infants’ physiological responses to the smell of different milks suggest they can distinguish between breastmilk and infant formula. We aimed to describe the profile of volatile compounds in preterm breastmilk and investigate how this differed from that of other preterm infant feeding options including pasteurised donor breastmilk, breastmilk with bovine milk-based fortifier, human milk-based products and various infant formulas. Methods: 47 milk samples (13 different infant formulas and 34 human milk-based samples) were analysed. Volatile compounds were extracted using Solid Phase Micro Extraction. Identification and relative quantification were carried out by Gas Chromatography with Mass Spectrometry. Principal Component Analysis (PCA) and one-way Analysis of Variance (ANOVA) with Tukey’s HSD (parametric data) or Conover’s post-hoc test (non-parametric data) were used as appropriate to explore differences in volatile profiles among milk types. Results: In total, 122 compounds were identified. Breastmilk containing bovine milk-based fortifier presented the highest number of compounds (109) and liquid formula the lowest (70). The profile of volatile compounds varied with 51 compounds significantly different (adjusted p<0.001) among milk types. PCA explained 47% of variability. Compared to preterm breastmilk, the profile of volatile compounds in breastmilk with added bovine milk-based fortifier was marked by presence of fatty acids and their esters, ketones and aldehydes; infant formulas were characterised by alkyls, aldehydes and furans, and human milk-based products presented high concentrations of aromatic hydrocarbons, terpenoids and specific fatty acids. Conclusions: Sensory-active products of fatty acid oxidation are the major contributors to olfactory cues in infant feeds. Analysis of volatile compounds might be useful for monitoring quality of milk and detection of oxidation products and environmental contaminants. Further research is needed to determine whether these different volatile compounds have biological or physiological effects in nutrition of preterm infants.